Perdamaian Aceh Dalam Perspektif Maqasid Syariah - Danial (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
Peace in Aceh is the aspiration of the people of Aceh and the Indonesian nation to get out of the protracted civil conflict. This research examines Aceh's peace from the perspective of maqasid sharia. This article is a qualitative study with a sharia maqasid approach. The data used in this study is divided into two, primary data and secondary data. The primary data was obtained from the al-Quran, while the secondary data was obtained from books, journals, and other articles related to the selected title. The research shows that peace in Aceh is still at the lowest level of the four dictions for peace used in the al-Quran; salam, sulhu, dzimmah and aman. This is because the peace in Aceh is still at the boundary of resolving disputes between two or more disputing parties. Then the maqasid sharia index in the aftermath of Aceh's peace is still on the mere maintenance of religion (din) and soul (nafs). There are still many empty spaces that need to be of concern to the government and society so that peace in Aceh is by maqasid sharia.